Viral Diversity in Benthic Abyssal Ecosystems: Ecological and Methodological Considerations - Umberto Rosani; Cinzia Corinaldesi; Gabriella Luongo; Marco Sollitto; Simeone Dal Monego; Danilo Licastro; Lucia Bongiorni; Paola Venier; Alberto Pallavicini; Antonio Dell’Anno (Viruses, 2023)
Viruses are the most abundant ‘biological entities’ in the world’s oceans. However, technical and methodological constraints limit our understanding of their diversity, particularly in benthic abyssal ecosystems (>4000 m depth). To verify advantages and limitations of analyzing virome DNA subjected either to random amplification or unamplified, we applied shotgun sequencing-by-synthesis to two sample pairs obtained from benthic abyssal sites located in the North-eastern Atlantic Ocean at ca. 4700 m depth. One amplified DNA sample was also subjected to single-molecule long-read sequencing for comparative purposes. Overall, we identified 24,828 viral Operational Taxonomic Units (vOTUs), belonging to 22 viral families. Viral reads were more abundant in the amplified DNA samples (38.5–49.9%) compared to the unamplified ones (4.4–5.8%), with the latter showing a greater viral diversity and 11–16% of dsDNA viruses almost undetectable in the amplified samples. From a procedural point of view, the viromes obtained by direct sequencing (without amplification step) provided a broader overview of both ss and dsDNA viral diversity. Nevertheless, our results suggest that the contextual use of random amplification of the same sample and long-read technology can improve the assessment of viral assemblages by reducing off-target reads.